2015
DOI: 10.1039/c4cy01504e
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of metal oxide catalysts in the synthesis of N-phenylpropionamide from propanoic acid and aniline

Abstract: The reactivities of various commercial and lab-made oxide samples (e.g., γ-Al 2 O 3 , CeO 2 , ZrO 2 and TiO 2 ) in the heterogeneous catalytic synthesis of N-phenylpropionamide (T, 383 K) from aniline and propanoic acid have been investigated. All the materials studied drive the direct synthesis of the amide to an extent depending on both the chemical and structural properties. A 0th-order kinetic dependence on the substrate concentrations suggests that the reaction proceeds via a Langmuir-Hinshelwood (L-H) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…This can be rationally interpreted from previously reported cases of catalytic amidation between amino and carboxyl groups by the solid-base properties of ZnO. [33][34][35] We show a schematic illustration of the catalytic amidation from the formed ion pairs between the AAC molecules and the excessive FA + cations in Fig- ure 3D. Generally, for the solution-processed ZnO films, there are unsaturated Lewis acid-base pairs on the imperfect surface, of which the exposed Zn 2+ cations and the O 2À anions act as Lewis acid and Lewis base sites, respectively.…”
Section: Ll Open Accesssupporting
confidence: 69%
“…This can be rationally interpreted from previously reported cases of catalytic amidation between amino and carboxyl groups by the solid-base properties of ZnO. [33][34][35] We show a schematic illustration of the catalytic amidation from the formed ion pairs between the AAC molecules and the excessive FA + cations in Fig- ure 3D. Generally, for the solution-processed ZnO films, there are unsaturated Lewis acid-base pairs on the imperfect surface, of which the exposed Zn 2+ cations and the O 2À anions act as Lewis acid and Lewis base sites, respectively.…”
Section: Ll Open Accesssupporting
confidence: 69%
“…This study follows our previous work [20,28,31] where we developed different titaniacontaining composite catalysts for this reaction. The main problems with these catalysts were (i) the relatively fast catalyst deactivation due to product inhibition, as a result of a strong product adsorption on the titania surface and (ii) limited reaction rate.…”
Section: Introductionmentioning
confidence: 88%
“…Chaudhari et al [30] studied the amide synthesis over acids and sulfated tungstates, and identified that catalytic activity significantly depends on the acid type. Arena et al [31] showed the following reaction rate sequence is observed TiO2 (P25) > ZrO2 ≈ CeO2 > γ-Al2O3 caused by the chemical and surface properties of the catalysts. To the best of our knowledge however, there is very little systematic studies about the effect of sulfation treatment on the direct amide synthesis reaction rates to allow for efficient catalyst development.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous catalysts employing other transition metals are also known and can offer simpler alternatives to systems that require intricate ligands. Iron [97] and various metal oxides [98] (most successfully TiO ) supported on silica having been reported, under neat conditions for the former free system. [97] Another report of heterogeneous catalysis employed silver/iron nanoparticles.…”
Section: Other Metalsmentioning
confidence: 99%